Addressing Crimes of Passion with the Deep-Self View of Moral Responsibility - Parish, Elijah (Stance: an international undergraduate philosophy journal, 2023)
In this paper, I summarize and object to the “deep-self” view of moral responsibility as laid out by Susan Wolf in “Sanity and the Metaphysics of Responsibility.” My objection centers on how our intuitions regarding crimes of passion conflict with the conclusions drawn by the deep-self view. I then proceed to sketch out three possible responses which can be made by an adherent to the deep-self view and make my recommendations on how such adherents should proceed in further understanding moral responsibility.